Implementasi Sistem Odoo Proses Procurement dan Production Menggunakan Metode RAD di UMKM Dapurbeta - Adisty, Mariska Tiara; Budiyono, Avon (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research focuses on implementing an Odoo-based Enterprise Resource Planning (ERP) system for the procurement and production processes of UMKM Dapurbeta using the Rapid Application Development (RAD) method. In today’s competitive business environment, particularly in the food and beverage sector, SMEs must adopt technology that enhances operational efficiency. The ERP system integrates data and information into a centralized platform, tailored through a fit gap analysis to meet the specific needs of UMKM Dapurbeta. The implementation includes the purchase and production modules, following three RAD stages: requirement planning, system design, and implementation. Results indicate that the Odoo-based ERP system effectively documents and controls procurement and production, optimizes raw material management, and reduces costs. Integration and blackbox testing confirm that the system meets all specified requirements. This ERP implementation significantly improves the speed and accuracy of operations, enhances inventory control, and boosts the competitiveness of UMKM Dapurbeta. It also integrates previously isolated business processes, making them more structured and efficient. The integration with WhatsApp automates communication with vendors by generating and sending RFQs and POs, further streamlining operations. Additionally, the raw material forecasting feature helps determine optimal stock levels, mitigating risks of overstocking or understocking. In conclusion, the ERP system enables UMKM Dapurbeta to better manage costs, raw material usage, and operational standards, ensuring sustained competitiveness in a highly competitive market.